UNGKAPAN MAKIAN DALAM BAHASA MINANGKABAU DI NAGARI KURAI TAJI KECAMATAN PARIAMAN SELATAN - Nadia Risni; Novia Juita; Ermawati Arief (Jurnal Bahasa dan Sastra, 2013)
The purposes of this article were to: 1) describe the form of invective in Minangkabau language, 2) describe the context of using invective expressions, and 3) describe the function of using  invective expressions in Nagari Kurai Taji South of Pariaman. The data of this study is the expressions used invective language of Minangkabau society in Nagari Kurai Taji South of Pariaman district. The data source of this research is the speech of informants in Nagari Kurai Taji South Pariaman district. The finding of the study is eksplained three things, namely 1) the form of invective, 2) the context of using invevtive expression, and 3) the functions of using invective expressions.The the form of invective consists of words and phrases. The form of invective can be categorized: nouns, verbs, adjectives. Cussthe contextof four, namely: (1)higher position speakers and familiar relationship, (2)a higher position speakers and donot close, (3)inferior speakers and familiar relationship, (4)inferior speakers and do notyet familiar. Function invective expression consists of:(1)express their resentment,(2)strong angerand extreme, (3)as ajo keor comedy purposes, (4)a means of expressing in timacy in relationships, (5)contempt, (6)expressed frustration and annoyance, and (7)as a means of disclosure as tonishment.